2017
DOI: 10.1186/s12940-017-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of environmental pollutants is a risk factor for breast cancer in Inuit: a case control study

Abstract: BackgroundEnvironmental Persistent Organic Pollutants (POPs) can alter the hormone homeostasis by mimicking, interfering or blocking the function of hormones; moreover POPs are hypothesized to modify the risk of breast cancer. The association between POPs and breast cancer has been widely studied but the conclusions are inconsistent. The present study examined the associations between serum levels of POPs and breast cancer with focus on the highly exposed Greenlandic Inuit population.MethodsThe study design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 52 publications
9
68
2
Order By: Relevance
“…All cases and 31 controls from our study were then included in a larger case-control study which involved overall 97 BC cases and 93 controls from the Inuit population. 16 This second study found a positive association between both PFOS and PFOA serum levels and BC risk, with no difference between ER− and ER+ cases. Although pointing toward the same results, when comparing these studies with our, some differences in the study design and in the study population have to be considered.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…All cases and 31 controls from our study were then included in a larger case-control study which involved overall 97 BC cases and 93 controls from the Inuit population. 16 This second study found a positive association between both PFOS and PFOA serum levels and BC risk, with no difference between ER− and ER+ cases. Although pointing toward the same results, when comparing these studies with our, some differences in the study design and in the study population have to be considered.…”
Section: Discussionmentioning
confidence: 73%
“…A case‐control study including 31 BC cases and 115 controls, selected from an Inuit population in Greenland, found that BC risk was positively associated with PFOS serum concentrations, although no stratification according to hormone receptor status was performed. All cases and 31 controls from our study were then included in a larger case‐control study which involved overall 97 BC cases and 93 controls from the Inuit population . This second study found a positive association between both PFOS and PFOA serum levels and BC risk, with no difference between ER− and ER+ cases.…”
Section: Discussionmentioning
confidence: 92%
“…Data on other classes of POPs such as polybrominated diphenyl ethers (PBDEs) and per-and poly-fluoroalkyl substances (PFASs) remain scarce and inconsistent [12][13][14][15][16][17][18][19][20][21][22]. Five studies using post-diagnostic samples have investigated serum or adipose-level PBDEs in relation to breast cancer risk [12,[14][15][16]22].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas positive associations were reported for a few PBDE congeners such as BDE-47, BDE-100, and BDE-153 in an area in China highly contaminated from electronic waste recycling [12], and suggestive positive associations were reported for BDE-47 in Alaska Native women [15] and young Canadian women [22], two studies conducted among general populations in California [14,16] reported no associations. Results on PFASs have also been mixed, with studies reporting positive associations for five PFAS compounds among Greenland Inuits [20], weak positive association for a PFAS compound perfluorooctane-sulfonamide (PFOSA) and non-significant inverse association for another PFAS compound among Danish women [17], and a positive association with estrogen receptor-positive breast cancer for perfluorooctane sulfonate (PFOS) in French women [21]; in addition, no associations were found for perfluorooctanoic acid (PFOA) in two studies conducted in an area near a chemical plant [18,19], nor for six PFAS compounds commonly detected in the general population in California [13]. Little is known about the role of these chemicals with respect to pathological changes along the cancer development pathway or cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation